Pelatihan Mengelola Homestay di Desa Wisata Donokerto - Damasdino, Fian; Saputra, Arif Dwi; Sinangjoyo, Nikasius Jonet; Angela Ariani, Angela; Anwari, Hamdan; Nur Islami, Mona Erythrea (Sekolah Tinggi Pariwisata AMPTA, 2020)
Donokerto village is one of the pioneering tourist villages that has good potential in terms of diversity of tourist attractions. In addition to tourist attraction, as a major factor triggering visits, homestay is one of the main strategic sources of income to be taken into account in every tourism village management. Remembering Homestay is a basic necessity for every tourist who wants to visit the village for a longer time. As a tourism village that is being pioneered, Desa Donokerto does not yet have human or community resources that understand in the ins and outs of Homestay management. Therefore, the AMPTA Yogyakarta Tourism School in collaboration with PUM Netherlands Senior Experts held a community service with the theme